MAKNA KODE VISUAL DALAM SCENE FILM ANIMASI â€œ BATTLE OF SURABAYAâ€ - Hasbullah, Hasbullah; Yasa, Gede Pasek Putra Adnyana (Jurnal Bahasa Rupa, 2020)
The animated film "Battle of Surabaya" is one of the nation's children's work that is able to win various awards, both at national and international levels. In some scenes in this animated film, there is a visual code that contains information or messages delivered to the audience (audience). Through observing several scenes, it is found that there is a meaning of the visual codes contained in the scene. This study aims to analyze the aesthetic visual codes contained in the first, middle and end scenes of the animated film "Battle of Surabaya". Data collected through observation and literature study. Theories used as analysis are semiotics and postmodern aesthetic codes. The results of this study indicate that the meaning of the visual code in the animated film scene "Battle of Surabaya" namely: in the first scene, the action or action of the Indonesian government declared independence from the Dutch East Indies government as an act of the past that needed to be made; the scene is explaining the rejection of Indonesian independence, this action as the style of an animator in the sequence before and next; the final scene depicts the action of the main character (Musa) who unites the storyline sequence of the animated film "Battle of Surabaya", one of which implements the cultural value of please help as an act of popularizing Indonesian culture.